Correlational study on entrance exam results of bachelor in elementary education freshman students - LIZA D. GARCIA; GILBERT JOHN V. MONTAJES; DHINA B. DALISAY; RHEMAR PRAISE E. BRUFAL; ANJENER R. QUEZON; GIDO, NATHANIEL G. (International Journal of Multidisciplinary Research and Studies, 2023)
This study focuses on the senior high school general weighted average and the entrance exam results to determine whether there is a relationship between the variables at X-Community College. The study uses correlational design, the most suitable type of research methodology, and it focuses on the verbal and non-verbal portions of the Otis-Lennon School Ability Test (OLSAT). The findings show that females between the ages of seventeen and eighteen (17–18) and HUMMS strand graduates make up the majority of BEED freshmen in 2021–2022. According to the results, the majority of the students earned GWAs of 90 to 100 (90-100) and 85 to 90 (85-90), while only a small number of them earned GWAs of 80 to 84 (80-84) and 46.34 percent (46.34%) of them earned ratings of Below Average and Low Average. Only two-point forty-four percent (2.44%) of the respondents received a High Average rating score on their college entrance exam results, compared to four-point eighty-eight percent (4.88%) of them who had an Average rating score. It revealed that the mean increases in the senior high school GWA and the scores on college entrance exams have only a weakly favorable link. It has been determined that there is little correlation between senior high school GWA and the outcomes of the entrance exams. The general weighted average has no consequence on or impact on their general weighted average, the statement emphasizes.